The young, the restless, and the dead : interviews with Canadian filmmakers - Melnyk, George (Wilfrid Laurier University Press, 2008)
The Young, the Restless, and the Dead captures the spirit of Canadian filmmakers through interviews with the most accomplished and dynamic of yesterday's, today's, and tomorrow's film greats. Funny, provocative, and enlightening, the filmmakers reflect on their careers and explore with the interviewers the issues that challenge them. This book features an interview with a late director (Jean-Claude Lauzon) whose work is recognized in the canon as outstanding; interviews with filmmakers who are accomplished in their fields and have to their credit a sizeable body of work (Blake Corbet, Andre.
Keywords: Motion picture producers and directors -- Canada -- Interviews.; Motion pictures -- Canada -- History.; Motion picture producers and directors -- Canada -- Biography.; Producteurs et réalisateurs de cinéma -- Canada -- Entretiens.; Cinéma -- Canada -- Histoire.; Producteurs et réalisateurs de cinéma -- Canada -- Biographies.; PERFORMING ARTS -- Film & Video -- Reference.; Motion picture producers and directors; Motion pictures; Canada; "Each volume in this series will contain eight to ten interviews"--P. viii; "Multi-User"; Biographies; History; Interviews; Biographies.